2020
DOI: 10.1002/ieam.4325
|View full text |Cite
|
Sign up to set email alerts
|

Methods Matter: Methods for Sampling Microplastic and Other Anthropogenic Particles and Their Implications for Monitoring and Ecological Risk Assessment

Abstract: To inform mitigation strategies and understand how microplastics affect wildlife, research is focused on understanding the sources, pathways, and occurrence of microplastics in the environment and in wildlife. Microplastics research entails counting and characterizing microplastics in nature, which is a labor-intensive process, particularly given the range of particle sizes and morphologies present within this diverse class of contaminants. Thus, it is crucial to determine appropriate sampling methods that bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 28 publications
1
50
1
Order By: Relevance
“…For example, many surveys of microplastics in surface water have employed coarse‐mesh nets (e.g., manta, neuston), which are effective at monitoring larger particles (300–500 µm) but not microfibers. A comparison of methods found higher proportions of microfibers compared to other particle morphologies in bulk water versus manta sampling methods (Hung et al, 2021; Tamminga et al, 2019). Thus, in many studies that have used coarse mesh or sieves, microfibers are likely underestimated.…”
Section: Resultsmentioning
confidence: 99%
“…For example, many surveys of microplastics in surface water have employed coarse‐mesh nets (e.g., manta, neuston), which are effective at monitoring larger particles (300–500 µm) but not microfibers. A comparison of methods found higher proportions of microfibers compared to other particle morphologies in bulk water versus manta sampling methods (Hung et al, 2021; Tamminga et al, 2019). Thus, in many studies that have used coarse mesh or sieves, microfibers are likely underestimated.…”
Section: Resultsmentioning
confidence: 99%
“…Much of the overall data on MP has been gained from overall a limited number of sampling studies at different locations, from which overall quantities of MP were derived using different models. It has been shown that different sampling techniques can lead to quite different results in the detection and quantification of MP in the environment [54] [55] and not in all areas is a consistent sampling technique for a matrix in use. In recent times, micro-Raman detection has been used to detect MP particles as small as 1 μm in size [56].…”
Section: Introductionmentioning
confidence: 99%
“…Important points for a standard test, pointed out by J€ onsson et al (2018), are as follows: a) vacuum cleaning of the surfaces prior to test to ensure that superficial dust and already loose fibres are removed, b) cutting the sample by laser to ensure that there is no loss of fibres from the cut edges, c) the use of steel balls inside the bag, which aligns the test with the industry standard for testing colour fastness. Strict cleanliness in the environs of the test is also essential, in view of the omnipresence of microplastic fibres in today's environment (Hung et al, 2021;Brander et al, 2020).…”
Section: Simulation Studiesmentioning
confidence: 99%